Analysis of errors of google translate for translating social work terminology from Vietnamese to English - Hanh, Vo Thi My (Edelweiss Applied Science and Technology, 2025)
This research investigates the errors produced by Google Translate in rendering Vietnamese social work terminology into English. A combination of statistical, classification, analytical, and descriptive methods was applied to ensure a comprehensive evaluation. The data set consists of 2,344 Vietnamese terms compiled from a specialized social work dictionary, along with their English equivalents generated by Google Translate. These translation outputs were examined and systematically categorized according to levels of equivalence and types of errors. The findings indicate that the most common and significant issues include conceptual mistranslation, breaches of the principle of brevity, and syntactic inaccuracies. Such recurring problems highlight the limitations of machine translation in specialized domains where terminological accuracy is essential. The outcomes of this study provide a valuable reference for linguists, translators, and researchers, offering practical insights for addressing challenges related to new and evolving terminology in the field of social work. Ultimately, the research underscores the necessity of human expertise in ensuring precise and contextually appropriate translation.